The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1152/ajpendo.00044.2013
|View full text |Cite
|
Sign up to set email alerts
|

Both aerobic exercise and resveratrol supplementation attenuate doxorubicin-induced cardiac injury in mice

Abstract: Because doxorubicin (DOX)-containing chemotherapy causes left ventricular (LV) dysfunction and remodeling that can progress to heart failure, strategies to alleviate DOX cardiotoxicity are necessary to improve health outcomes of patients surviving cancer. Although clinical evidence suggests that aerobic exercise training (ET) can prevent cardiotoxicity in patients undergoing DOX chemotherapy, the physiological mechanisms involved have not been extensively studied, nor is it known whether compounds [such as res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(136 citation statements)
references
References 51 publications
5
131
0
Order By: Relevance
“…The pivotal role played by mitochondrial dysfunction in doxorubicin cardiotoxicity is, furthermore, revealed by the fact that activation of mitochondrial function or biogenesis by various agents, such as frataxin overexpression, exercise training or resveratrol, are sufficient to protect against doxorubicin cardiotoxicity and cardiac dysfunction. 45,46 In the present study, doxorubicin cardiotoxicity was observed only in males and was accompanied by early mitochondrial dysfunction again emphasizing the role of mitochondrial dysfunction in doxorubicin cardiotoxicity and further suggesting a possible role in sex differences.…”
Section: Discussionsupporting
confidence: 62%
“…The pivotal role played by mitochondrial dysfunction in doxorubicin cardiotoxicity is, furthermore, revealed by the fact that activation of mitochondrial function or biogenesis by various agents, such as frataxin overexpression, exercise training or resveratrol, are sufficient to protect against doxorubicin cardiotoxicity and cardiac dysfunction. 45,46 In the present study, doxorubicin cardiotoxicity was observed only in males and was accompanied by early mitochondrial dysfunction again emphasizing the role of mitochondrial dysfunction in doxorubicin cardiotoxicity and further suggesting a possible role in sex differences.…”
Section: Discussionsupporting
confidence: 62%
“…36,39 However, it is not known whether resveratrol can be used to treat established pressure-overload-induced HF and prevent or reverse cardiac and vascular remodeling induced by HF. Using the TAC mouse model, we made several key findings starting with resveratrol treatment significantly improving median survival of mice with HF.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyocytes derive as much as 90% of ATP from mitochondrial oxidative phosphorylation, and thus, are extremely sensitive to the effects of anthracyclines. In animal models, exercise has been shown to mitigate cardiotoxicity [56] in part alleviating the effects on mitochondrial function [57] . While overt toxicity may not be evident, other tissues may suffer from impairments.…”
Section: Compositionmentioning
confidence: 99%